If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12(y + -3) = 108 Reorder the terms: 12(-3 + y) = 108 (-3 * 12 + y * 12) = 108 (-36 + 12y) = 108 Solving -36 + 12y = 108 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '36' to each side of the equation. -36 + 36 + 12y = 108 + 36 Combine like terms: -36 + 36 = 0 0 + 12y = 108 + 36 12y = 108 + 36 Combine like terms: 108 + 36 = 144 12y = 144 Divide each side by '12'. y = 12 Simplifying y = 12
| 3k-7j=8 | | 2(v-8)-7V=19 | | 4x-4=9x-21 | | 3y-ax=12 | | 2(4x-1)=3/2x-1 | | 2/y-1/4=-1/6 | | y-8=-10(x+6) | | -(2)/(3)x=4 | | 1/x-4/5x=1 | | 14c-7-3=6+6c | | y+8=-(x+8) | | 14s-8s-3=15 | | 14c=10+6c | | 1=9f+x | | y-10=3(x-3) | | 33=16m-12-m | | 19n+21=21 | | 5b=-1 | | -x^4-4x=0 | | y+4=8(x-2) | | 2-16t=-12t+12 | | 2.5-3.1t=21.05 | | https://hcps.blackboard.com/bbcswebdav/pid-1004819-dt-content-rid-2152875_1/xid-2152875_1 | | y-6=-8(x-4) | | 60-6b=-89 | | 130+.5x=40+.8x | | 9y-5-y=35 | | 12-2x=-2(y-x)-12 | | -12y=2x-3 | | 3(3x+1)+4=-23 | | 7.4x+1y=801900000 | | P=2.6x+33.0 |